Moving towards political participation: The moderation of Moroccan Salafis since the beginning of the Arab Spring - Mohammed Masbah (Stiftung Wissenschaft und Politik (SWP), 2013)
Salafis, including former "Salafi-Jihadis", have become a presence in the public sphere through their participation in the protests - side-by-side with secular forces - of the so-called 20 February Movement. There are also numerous indications that Salafis will play a role in shaping Morocco's future political landscape, albeit while proposing less radical objectives than what they used to profess. The trend is leading towards greater acceptance of political plurality, more cooperation with moderate Islamists, and less aggressive attitudes towards seculars and Western governments. Most importantly, they are explicitly renouncing violent means in the domestic power struggle. Moroccan Salafis have begun aiming at assuming a political role, attempting to influence policy-making, and are increasingly prepared to play by the rules of the democratic game - thus following the example set by their peers in other Arab countries such as Egypt
Keywords: 320